General or specific? The memory–experience gap for individuals diagnosed with a major depressive disorder or a social phobia diagnosis, and individuals without such diagnoses. Issue 9 (21st October 2019) - Rinner, Marcia T. B.; Meyer, Andrea H.; Mikoteit, Thorsten; Hoyer, Jürgen; Imboden, Christian; Hatzinger, Martin; Bader, Klaus; Lieb, Roselind; Miché, Marcel; Wersebe, Hanna; Gloster, Andrew T.
ABSTRACT: Psychological treatment and assessment necessarily rely on patients' recall. Yet several empirical studies have documented a gap between memory and real-life experience (i.e., memory–experience gap; MeG). We investigated and compared the MeG of sadness, social anxiety, happiness, and physical activity for participants diagnosed with a major depressive disorder (MDD), a social phobia (SP), and participants without such diagnoses (CG). The study included 118 participants diagnosed with a MDD, 47 with a SP, and 119 CG. Using event-sampling methods (ESM), participants were asked via smartphone to report their experiences throughout a week and then to recall those again retrospectively at the end of the study week. Results indicate significant differences in the MeG with respect to the experience that was salient to them (e.g., MDD group – sadness; SP group – social anxiety; CG group – happiness). Furthermore, all groups showed a MeG for physical activity and, the results indicate significant group differences in the magnitude of the MeGs. This study demonstrated the presence of a MeG in individuals in a MDD, SP, and CG group and in positive and negative affective experiences. Differential patterns across the samples contribute to a better understanding of this gap and its implications.